The Influence of Telegram Channels as a Knowledge-Sharing Medium on Students' Information Literacy Levels - Wulan Sri Wahyuni; Elva Rahmah (Darul Yasin Al Sys, 2026)
The rapid development of digital communication technologies has expanded the use of Telegram channels as knowledge-sharing media in higher education; however, their contribution to students’ information literacy remains insufficiently examined. This study aimed to analyze the influence of Telegram channel utilization as a knowledge-sharing medium on the information literacy of students in the Library and Information Science Study Program at Universitas Negeri Padang. A quantitative explanatory approach with a causal-associative design was employed. The study involved 72 students from a population of 258, with the sample size determined using the Slovin formula. Data were collected through a structured questionnaire and analyzed using descriptive statistics, Pearson correlation, simple linear regression, and the coefficient of determination with IBM SPSS Statistics 26. The findings indicated that both Telegram channel utilization and students’ information literacy were categorized as good. Telegram channel utilization had a positive and statistically significant effect on information literacy, with a correlation coefficient of 0.696 and a coefficient of determination of 48.4%, indicating that it explained 48.4% of the variation in students’ information literacy. The study concludes that Telegram channels can function effectively as knowledge-sharing media that support students’ ability to access, evaluate, and use information. These findings contribute empirical evidence to the literature on digital knowledge sharing and provide practical implications for higher education institutions seeking to optimize digital communication platforms to strengthen information literacy and collaborative learning.